Transplante de fração total de células mononucleares ou fração vascular estromal associada à membrana celulósica em feridas cutâneas experimentais de coelhos - Treichel, Tiago Luís Eilers (2010)
The skin, tegument which covers the body of animals, presents various important functions to the organism. The maintenance of its integrity is fundamental to prevent penetration of microorganisms and exit of liquids essential to life maintenance. Due to its constant environment exposure, the skin is highly susceptible to trauma which can result in solutions of continuity. Excision of tumoral masses or infectious lesions, iatrogenic lesions, extensive surgical complications, burns, automobile accidents, snake bites or insect stings, injection of irritant drugs or even gunshots or traps are causes that can result in lesions in any area of the animal‟s skin. The healing of wounded skin should be fast, in order to assure the return of its integrity, however, some complications can occur as in limb lesions or patients with extensively burned areas. Many alternatives are searched for, aiming to reduce repair time and to guarantee a functional and esthetically acceptable scar. One option to repair injured tissues which is ever more viable is cellular therapy with adult stem cells. To carry out this experiment, 20 rabbits were randomly divided in four groups with five animals each. Group A did not receive any treatment; group B received only one cellulose membrane; and groups C and D, in addition to receiving the membrane, were submitted to autologous transplant of total mononuclear cell fraction (TMCF) from bone marrow or stromal vascular fraction (SVF) from adipose tissue, respectively. The aims of this study consisted in evaluating the transplant of these fractions, associated with the use of cellulose membrane. Therefore, after induction of the experimental cutaneous wound in all the animals, this was followed by application of the membrane and autogenous TMCF transplant, with total cell value between 6,92 x 106 and 4,91 x 107 and a viability of 82 to 97%, or SVF, with total cell value between 9,6 x 105 and 6,5 x 106 and a viability of 66 a 87%. The animals were submitted to photographic evaluation, measurement of wounds and biopsy at 7, 14 and 21 postoperative days. At the end of the evaluation period, the three treated groups presented significant statistical difference of wound area in relation to the control group, and the group which received SVF from adipose tissue presented the shortest wound healing time.